Considerations on D-mannose Mechanism of Action and Consequent Classification of Marketed Healthcare Products - Scaglione, Francesco; Musazzi, Umberto M.; Minghetti, Paola (Frontiers in Pharmacology, 2021)
Urinary tract infections (UTIs) are very common disorders that affect adult women. Indeed, 50% of all women suffer from UTIs at least one time in their lifetime; 20–40% of them experience recurrent episodes. The majority of UTIs seems to be due to uropathogenic Escherichia coli that invades urothelial cells and forms quiescent bacterial reservoirs. Recurrences of UTIs are often treated with non-prescribed antibiotics by the patients, with increased issues connected to antibiotics resistance. D-mannose, a monosaccharide that is absorbed but not metabolized by the human body, has been proposed as an alternative approach for managing UTIs since it can inhibit the bacterial adhesion to the urothelium. This manuscript discusses the mechanisms through which D-mannose acts to highlight the regulatory aspects relevant for determining the administrative category of healthcare products placed on the market. The existing literature permits to conclude that the anti-adhesive effect of D-mannose cannot be considered as a pharmacological effect and, therefore, D-mannose-based products should be classified as medical devices composed of substances.